Analisis Implementasi Restrukturisasi Utang Dengan Metode Debt To Equity Swap PT Palmars - Dela Febrianti; Astrini Aning Widoretno (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to determine whether the implementation of debt restructuring includes specific steps to get out of financial difficulties or not used in debt restructuring procedures with the debt to equity swap method. The research method used by the author in this research is qualitative research, namely data presented in descriptive form. The data collection methods in this research are interviews, observations, checklists and documentation. This research is a field research that aims to obtain primary data from researchers who work directly to PT Palmars as the object of research. The results showed that PT Palmars has implemented procedures in a structured and more specific manner.